Income tax : including tax planning and management assessment year 2024-25 - Mehrotra H C; Goyal, S P (Agra Sahitya Bhawan Publications, 2024)
Introduction and important definitions ;residence and tax liability(basis of charge); exemptions form tax(tax-free incomes) ;income from salaries ; income from Salaris(taxability of retirement benefits);income from house property; profits and gains of business or profession ; determination of income of certain business or profession on presumptive basis; depreciation and investment sloes ' capital gains ;income from other sources ; clubbing of income and aggregation of incomes or deemed incomes ;set-off or carry -forward and set-off of losses; deductions from gross total income while computing total income; agricultural income; rebates and reliefs of tax; computation of total income of individuals.
Keywords: Income Tax